Road Defects Analysis of Mulawarman Street STA 00+000 – 03+300 Using Pavement Condition Index (PCI) Method - Kurniawan, Musthofa Kamal; Sulistyo, Totok; Giarto, Rahmat Bangun (Civil Engineering Dept, Balikpapan State Polytechnics, 2002)
The Mulawarman Teritip – Gunung Tembak Balikpapan road is the main road connecting the city of Balikpapan and the district of Samboja and Sanga-Sanga. The purpose of this study was to determine the type and value based on the amount of road damage that occurred, so research was carried out in the form of an assessment to determine the level of road damage, before finally obtaining the cause and treatment that was suitable for the road segment. Observations on the Mulawarman Teritip – Gunung Tembak STA 15+250 to 18+550, aimed to research road conditions using the method of Pavement Condition Index (PCI). Analysis of the data obtained include: Survey data, Quantity (Quantity), Density (Density), Graph Deduct Value (DV), Total Deduct Value (TDV), Correct Deduct Value (CDV), Pavement Condition Index (PCI), and Repair Method. PCI value at Mulawarman Teritip – Gunung Tembak road obtained from the calculation is 74.5 in the category of Satisfactory, and the method of repair is done is road maintenance on a regular basis to improve quality and preserve the value of PCI.